Analysis of False Alarms on DVOR Equipment at I Gusti Ngurah Rai International Airport - Andre Rizky Sanjaya; Donna N.M. Sirait; Muhammad Caesar; Akbar Erwin Lumban Gaol (International Journal of Society and Law, 2024)
According to the Government Regulation of the Republic of Indonesia No.71 of 1996 concerning Airports article 9 Paragraph (1) it is explained that flight navigation facilities can include Non Directional Beacons (NDB), Doppler VHF Omni Range (DVOR), Instrument Landing System (ILS), Radio Detection and Ranging (RADAR). Airports must provide navigation facilities, especially the Doppler VHF Omni Range (DVOR), which is a flight aid that has unlimited (continuous) capabilities, and transmits combined radio signals, including Morse code and data that can enable receiver equipment on aircraft to acquire magnetic bearings. from the station to the airplane using the frequency due to the doppler effect, not the actual azimuth direction to the aircraft but information about the Doppler VHF Omni Range (DVOR) ground station point at I Gusti Ngurah Rai Airport. This study used a qualitative descriptive method with physical checking at the Denpasar Branch of Perum LPPNPI, there was an alarm on the Doppler VHF Omni Range (DVOR) equipment caused by a lightning strike which could not be controlled using LMMS due to failure in several modules. So researchers need to replace several modules affected by the Alarm, namely the LCU (Local Control Unit), CSU (Control Sector Unit), and ASU (Air STARTER UNIT) and do the finishing by checking the power and settings on the monitor, resulting in a Doppler VHF Omni Range (DVOR) adjustment. back to normal.